2008
DOI: 10.2353/ajpath.2008.070863
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Prevents Airway Mucus Hypersecretion Induced by Cigarette Smoke in Rodents and Humans

Abstract: We investigated the role of heme oxygenase-1 (HO-1), a powerful anti-inflammatory and anti-oxidant enzyme, in modulating cigarette smoke (CS)-induced mucus secretion. In both rats and mice, 5-day CS exposure increased HO-1 expression and activity, mucus secretion, MUCIN 5AC (MUC5AC) gene and protein expression, and local inflammation, along with up-regulation of dual oxidase 1 gene expression and both the activity and phosphorylation of the epidermal growth factor receptor, which is involved in MUC5AC inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Heme oxygenase 1 has been shown to inhibit IL‐13‐induced‐MUC5AC expression and more recently, this process was shown to be associated with reduced CLCA1 expression in human bronchial epithelial cells (Almolki et al. 2008; Mishina et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Heme oxygenase 1 has been shown to inhibit IL‐13‐induced‐MUC5AC expression and more recently, this process was shown to be associated with reduced CLCA1 expression in human bronchial epithelial cells (Almolki et al. 2008; Mishina et al. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In one antioxidant system, an increase in heme degradation by hemeoxygenase (HO-1) to biliverdin and bilirubin is a protective anti-inflammatory response to increased oxidative stress. Exposure to cigarette smoke (or its constituents) is known to increase the expression of HO-1 [34][35][36][37]. Plasma metabolomic profiles showed increased levels of heme, and decreased levels of bilirubin and biliverdin in SMK, relative to NTC, indicating a possible impairment of the heme degradation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that hemin, a substrate of HO-1, significantly increases the expression of HO-1 protein as well as its activity and ameliorates inflammation in a variety of animal models (29 -31). The competitive inhibitor Sn-protoporphyrin IX (SnPP) also induces the expression of HO-1 but blocks the enzymatic activity in both animal models and cultured cells, creating an opposite effect (32)(33)(34)(35). Because HO-1 has pleiotropic immunomodulatory effects, there are already numerous illustrations of therapeutic applications of HO-1 in multiple experimental models of IBD mediated by various immune mechanisms (36 -38).…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%